Analisis Penerapan Metode First In First Out ( Fifo ) Dan Average Untuk Penilaian Persediaan Kertas HVS Pada Muara Kaman Copy & Print Center Di Tenggarong - Widyasari, Nurtia; Palinggi, Yonathan; Hermanto, Muhammad (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purpose of this study was to compare the valuation of HVS paper inventories with the First In First Out (FIFO) method and the Average method in the Muara Kaman photocopy business in Tenggarong. The analytical tool used is descriptive analysis. The method of descriptive analysis is to describe the nature of something that has been going on at the time the research is being conducted and examines the causes of certain symptoms. Furthermore, this analysis uses the FIFO and Average methods in inventory valuation. The results of calculations using the average method produce cost of goods sold which is greater than the First In First Out (FIFO) method. On the other hand, the calculation using the First In First Out (FIFO) method will result in a higher ending inventory value than the average method. So if you want to report the value of current assets (especially inventory) is greater then you can use the FIFO method. Keywords: Inventory Valuation, FIFO, Average